Effect of the monocyte locomotion inhibitory factor (MLIF) produced by E. histolityca on cytokines and chemokine receptors in T CD4+ lymphocytes - SARA ROJAS-DOTOR; JULIA PÉREZ-RAMOS; JUAN ANTONIO GIMÉNEZ-SCHERER; FRANCISCO BLANCO-FAVELA; GUADALUPE RICO-ROSILLO (Biological Research, 2009)
Entamoeba histolytica produces Monocyte Locomotion Inhibitory Factor (MLIF), which may contribute to the delayed inflammation observed in amoebic hepatic abscesses. Leukocytes are affected through the modulation of cytokine expression and/or production. We evaluated the effects of MLIF on the activation and production of intracellular cytokines in human CD4+ T lymphocytes by flow cytometry. Cells were stimulated for 24 h with PMA, MLIF, or PMA+MLIF. Cellular activation was measured using anti-CD69. Th1/Th2 production was studied by the expression of intracellular cytokines and cytokine/chemokine receptors. MLIF increased CD69 and induced the over-expression of the IL-lß, IFN-γ, IL-2, IL-4, and IL-10 intracellular cytokines; PMA+MLIF inhibited Th1 cytokine (IFN-γ) and increased Th2 cytokines (IL-4 and IL-10). The co-expression of the cytokine and chemokine receptors IFN-γ/CCR5 and IL-1ß/CCR5 was inhibited by PMA+MLIF and Th2 co-expression was increased. MLIF effects varied depending on the conditions. MLIF alone activated the Th1 and Th2 cytokines and cytokine/receptor expression; however, PMA+MLIF increased the expression of Th2 but inhibited it in Th1.